Homer condensates orchestrate YAP–Wnt signaling crosstalk downstream of the Crumbs polarity complex - Siti Maryam J. M. Yatim; Linda Jiabao Woo; Yuhong Chen; Barbara Hübner; Alexander Ludwig (Proceedings of the National Academy of Sciences, 2026)
The Hippo pathway governs cell growth, proliferation, and differentiation and is frequently deregulated in cancer. Yes-associated protein (YAP) is the central transcriptional coactivator of the Hippo pathway and interacts with β-catenin to coordinate YAP–Wnt signaling crosstalk. Both pathways are modulated by diverse upstream signals including mechanical cues, cell density, and cell polarity, yet how such signals are integrated remains poorly understood. Here, we demonstrate that Homer scaffolding proteins coordinate YAP and Wnt signaling downstream of the Crumbs polarity complex. Homers interact directly via their EVH1 domains with the Crumbs component PATJ and the NDR kinase scaffold Furry-like (FRYL). Homers antagonize FRYL to promote YAP activation while cooperating with FRYL to enhance Wnt/β-catenin signaling, revealing pathway-selective regulation. PATJ, in contrast, recruits Homers to the cortex and restrains YAP activity. We further show that Homers form biomolecular condensates in nonpolarized epithelial and colorectal cancer cells, whose assembly and signaling properties are differentially modulated by PATJ and FRYL. Whereas FRYL promotes the formation of cytoplasmic droplets, PATJ drives the assembly of phase-separated compartments at or near the plasma membrane. Collectively, our findings establish Homer-driven phase separation as a tunable signaling mechanism to translate polarity cues into transcriptional output.